Test Gas Generation from Pure Liquids: An Application-Oriented Overview of Methods in a Nutshell - Yue Li; Tim Täffner; Michael Bischoff; Bernd Niemeyer (International Journal of Chemical Engineering)
The generation of test gas from pure liquids has a wide variety of applications in laboratory and field experiments, for which the quality of the test gas is of significance. Therefore, various methods for test gas generation have been designed. Each method has unique advantages and disadvantages. Thus, a short overview is presented within the scope of this paper. Furthermore, a common bubbler system is presented, which was built to generate test gas from volatile organic compounds for experimental usage in laboratory applications. An analysis is conducted with respect to the generated concentrations at different temperatures and flow rates of the diluting gas. Accuracy and stability of this method are investigated.